2023
DOI: 10.1038/s41556-023-01117-9
|View full text |Cite
|
Sign up to set email alerts
|

Metaboverse enables automated discovery and visualization of diverse metabolic regulatory patterns

Abstract: Metabolism is intertwined with various cellular processes, including controlling cell fate, influencing tumorigenesis, participating in stress responses and more. Metabolism is a complex, interdependent network, and local perturbations can have indirect effects that are pervasive across the metabolic network. Current analytical and technical limitations have long created a bottleneck in metabolic data interpretation. To address these shortcomings, we developed Metaboverse, a user-friendly tool to facilitate da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Reaction representations and multi-condition reaction component comparisons were prepared using Metaboverse (v0.9.0) 30 . Input proteomics and metabolomics were prepared by calculating the log 2 fold change and Benjamini-Hochberg corrected Student’s T-test statistic for each comparison.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction representations and multi-condition reaction component comparisons were prepared using Metaboverse (v0.9.0) 30 . Input proteomics and metabolomics were prepared by calculating the log 2 fold change and Benjamini-Hochberg corrected Student’s T-test statistic for each comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Examining the regulatory patterns of the composite metabolomic and proteomic effects of mechanoresponses in DMEM and HPLM 30 , we found that NAD(P)H photochemistry and stress response signatures of cells cultured in stiff HPLM microenvironments were associated with increased glutathione oxidation, suggesting that stiff microenvironments elicit more oxidative stress and PARP1 activity (Fig. S1G-H and S3A-C).…”
Section: Ecm Stiffness Enhances Metabolic Support Of Glycosylationmentioning
confidence: 99%
“…To understand the transcriptional reprogramming that occurs during the loss of mtFAS, and by extension, the interplay between dysfunctional mitochondrial and cell health, we reanalyzed an RNA-sequencing dataset ( Berg et al, 2023 ) generated from a yeast mutant lacking mtFAS function ( mct1 Δ) ( Schneider et al, 1997 ) before and after transitioning from glucose- to raffinose-containing medium—a manipulation that induces mitochondrial biogenesis. The canonical mitochondrial biogenesis transcriptional response was almost completely absent in the mct1 Δ cells, as evidenced by the lack of induction of mRNAs encoding subunits of the ETC and ATP synthase ( Figure 1—figure supplement 1A ).…”
Section: Resultsmentioning
confidence: 99%
“… ( A, B ) Heat map visualizing selected gene expression between wild-type (WT) and mct1 Δ using transcriptomics data from Berg et al, 2023 . Gene expression was measured at 0, 3, and 12 hr after switching from glucose containing media to raffinose containing media.…”
Section: Resultsmentioning
confidence: 99%